PENERAPAN MODEL CIPRO DALAM PEMBELAJARAN MENULIS TEKS PIDATO SISWA KELAS VIII SMP NEGERI 28 MUARO JAMBI - Sandi, Muhammad Sandi Kurniawan; Agus Setyonegoro; Hilman Yusra; Rasdawita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the CIPRO Model in learning to write speech texts among eighth-grade students at SMP Negeri 28 Muaro Jambi. The research focused on understanding how the model supports students’ writing skills, critical thinking, and participation in the learning process. This study employed a qualitative descriptive approach with a field study design to explore the learning process in its natural context. Data were collected through participatory observation, semi-structured interviews, and documentation involving one Indonesian language teacher and six representative students selected purposively based on different academic ability levels. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which included data reduction, data display, and conclusion drawing through triangulation and member checking techniques. The findings revealed that the implementation of the CIPRO Model encouraged students to participate more actively in learning activities, improved their ability to organize ideas systematically, and strengthened their argumentative writing skills. The stages of identifying problems, gathering information, formulating arguments, collaboration, and presenting results enabled students to develop more structured and persuasive speech texts. In addition, collaborative discussions and reflective learning activities increased students’ confidence and critical thinking abilities during the writing process. However, the study also identified several challenges, particularly limited instructional time and differences in students’ academic abilities during the implementation process. This study contributes to the development of process-based and participatory learning models in Indonesian language education, particularly in speech-text writing instruction at the junior high school level. The findings imply that the CIPRO Model can be used as an alternative instructional strategy to create more interactive, contextual, and student-centered learning environments. Future studies are recommended to examine the effectiveness of the model in broader educational contexts and through mixed-method approaches.